Adenosine receptor stimulation by polynucleotides (PDRN) reduces inflammation in experimental periodontitis. (3rd October 2012) - Bitto, Alessandra; Oteri, Giacomo; Pisano, Michele; Polito, Francesca; Irrera, Natasha; Minutoli, Letteria; Squadrito, Francesco; Altavilla, Domenica
Abstract: Aim: Adenosine receptors modulate inflammation in periodontal tissues. No data are available regarding the effects of adenosine A2A receptor stimulation in experimental periodontitis (EPD). The aim of this study was to investigate the effects of polynucleotides (also known as polydeoxyribonucleotide, PDRN), a ligand of A2A receptor, in EPD in rats. Materials and Methods: EPD was induced ligating the cervix of the lower left first molar. Sham‐EPD had no ligature. After 7 days, EPD animals were randomized to a daily treatment with vehicle gel or 0.75% PDRN gel or PDRN gel with a specific A2A antagonist (DMPX). Treatments lasted 7 days. Animals were then euthanized and the periodontium and surrounding gingival tissue were excised for histological evaluation and bio‐molecular analysis of inflammatory (p‐JNK, p‐ERK, TNF‐α, IL‐6, HMGB‐1) and apoptotic proteins (BAX and Bcl‐2). Results: Vehicle‐treated EPD rats showed severe inflammatory infiltrate in both gingival and periodontal ligament, as well as an enhanced expression of p‐JNK, p‐ERK, TNF‐α, IL‐6, HMGB‐1 and BAX and a reduction in Bcl‐2. PDRN gel restored the histological features, blunted inflammatory and apoptotic proteins expression and preserved Bcl‐2 expression. DMPX abrogated PDRN positive effects. Conclusion: Our data suggest that adenosine receptor stimulation by PDRN might represent a new therapeutic strategy for periodontitis.